ABNORMAL PSYCHOLOGY - SHARMA, SAMRITI (SOURABH PUBLISHING HOUSE 4263/3, ANSARI ROAD, DARYAGANJ, NEW DELHI - 110002``, 1993)
Abnormal psychology is concerned with mental and emotional disorders and with certain incompletely under stood normal phenomena. this books provide readers with a comprehensive and up to date real world overview of the abnormal psychology field, by building on the strengths of exiting theoretical system and clinical methods. It focuses on maladaptive behaviors. a product of the interaction between personal vulnerabilities and re-silience. This book is beneficial for individuals interested in the fields of abnormal psychology, abnormal behavior and psychopathology.